Experimental evidence showing that physician guidance promotes perceptions of physician empathy. Issue 3 (2nd July 2016) - Hans, Daniel Russell; Dubé, Priyanka; Wasserman, Jason Adam
ABSTRACT: Background : This article reports a study that assessed the link between physician guidance and perceptions of empathy. Previous literature suggests that patients prefer medical decision making to be a collaborative process. However, no study has specifically tested how physician guidance affects the way the patient perceives his or her physician's empathy. As a period of laissez-faire autonomy appears to be drawing to a close, it will be important to understand what kinds of guidance have positive effects on the physician-patient relationship.Methods: This study used a matched-vignette design to investigate whether individuals perceive a physician who provides an opinion on the best course of action for a patient as more empathic than one who does not. Surveys were administered at local YMCAs to capture the widest demographic possible, with participants randomly assigned to one of two vignettes.Results: Findings suggest that patients may indeed view physicians who guide medical decision making as more empathic. Specifically, those participants assigned the vignette in which the physician guided the patient's decision rated that physician as more empathic, even while controlling for gender.Conclusions: Some forms of physician input into patient decision making clearly improve patients' perceptions of physicians' empathy. However, more research is needed as to what types of involvement with patient decisions promote positive perceptions of physicians and under what conditions.